2019
DOI: 10.3390/ma12152476
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Strategies for Electrospun Gelatin Scaffolds

Abstract: Electrospinning is an exceptional technology to fabricate sub-micrometric fiber scaffolds for regenerative medicine applications and to mimic the morphology and the chemistry of the natural extracellular matrix (ECM). Although most synthetic and natural polymers can be electrospun, gelatin frequently represents a material of choice due to the presence of cell-interactive motifs, its wide availability, low cost, easy processability, and biodegradability. However, cross-linking is required to stabilize the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 113 publications
2
142
0
1
Order By: Relevance
“…Various coupling or cross-linking agents such as glutaraldehyde (GA), formaldehyde, and methacryloyl derivatives have been used to strengthen the hydrolytic and enzymatic stabilities [13,14] and the mechanical properties of gelatins. Although it has been reported that GA treatment increases the mechanical strength and resistance to degradation of gelatin [15,16], the cytocompatibility of GA-treated gelatin tends to be reduced [17][18][19]. As a result, chemical treatments reduce the usefulness of gelatin as a scaffold for tissue regeneration and drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Various coupling or cross-linking agents such as glutaraldehyde (GA), formaldehyde, and methacryloyl derivatives have been used to strengthen the hydrolytic and enzymatic stabilities [13,14] and the mechanical properties of gelatins. Although it has been reported that GA treatment increases the mechanical strength and resistance to degradation of gelatin [15,16], the cytocompatibility of GA-treated gelatin tends to be reduced [17][18][19]. As a result, chemical treatments reduce the usefulness of gelatin as a scaffold for tissue regeneration and drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin can be tailor modified to suit the drug being loaded and is therefore a good candidate for oral delivery of hydrophobic chemotherapeutics [11]. Another valuable advantage of gelatin modification is the incorporation of targeting moieties for targeted oral delivery; to spare healthy cells and ensure that after intestinal drug absorption, only the tumour cells are targeted and destroyed [12][13][14]. There has been a significant amount of research done into the use of gelatin for nanoformulations for the delivery of DNA molecules, cancer and tuberculosis agents.…”
Section: Gelatinmentioning
confidence: 99%
“…Schematic representation of crosslinking methods used to formulate gelatin nano-materials. Adapted and modified with permission from[14].…”
mentioning
confidence: 99%
“…Of these, cross-linking using chemical agents such as glutaraldehyde (GTA), 4-arm polyethylene glycol succinimidyl glutarate (4SP), diphenyl phosphoryl azide (DPPA), genipin, and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) are most commonly used, because other cross-linking methods do not cross-link collagen well enough to increase mechanical stability and slow down membrane degradation [ 34 , 35 , 36 ]. Although several studies have reported that chemical cross-linking methods can trigger foreign body response due to chemical agent residues [ 33 , 37 ], EDC tends to lower cytotoxicity, because it does not remain as part of the linkage, and is converted to water-soluble urea derivatives that are relatively noncytotoxic [ 31 , 38 , 39 , 40 ]. In a previous study in which two different bone grafts were implanted into rat calvarial defects with EDC-cross-linked collagen membrane, animals showed excellent bone regeneration, no inflammatory reaction, and no membrane collapse [ 41 ].…”
Section: Introductionmentioning
confidence: 99%